2021
DOI: 10.1097/ju.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Lamina Propria Invasion Diagnosed by En Bloc Transurethral Resection is a Significant Predictor of Progression for pT1 Bladder Cancer

Abstract: Purpose: T1 bladder cancer is characterized by high recurrence and aggressive progression. Muscularis mucosae invasion may be a prognostic factor for progression, but the limitations of conventional transurethral resection of bladder tumors make diagnosis difficult. We correlated degree of invasion with oncologic outcome and evaluated the utility of pathological diagnosis following en bloc resection of bladder tumors. Materials and Methods: We retrospectively analyzed the records of 123 consecutive patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…3 Recent evidence underlines its importance in accurately diagnosing the degree of vertical lamina progression, with the latter having an impact on progression-free survival in patients diagnosed with pT1 bladder cancer. 12 Moreover a study of NMIBC 123 patients (TURBT, n = 91, ERBT, n = 32) with pT1 disease showed that both diagnostic time and interobserver variability for T1 sub-staging favor ERBT. 13 In light of the plethora of technological advancements there is a multitude of available ways to perform ERBT ranging from use of a modified J-loop electrode and Collins knife to specifically designed bipolar electrocautery loops and HybridKnife ® endoscopic submucosal hydro-dissection.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent evidence underlines its importance in accurately diagnosing the degree of vertical lamina progression, with the latter having an impact on progression-free survival in patients diagnosed with pT1 bladder cancer. 12 Moreover a study of NMIBC 123 patients (TURBT, n = 91, ERBT, n = 32) with pT1 disease showed that both diagnostic time and inter-observer variability for T1 sub-staging favor ERBT. 13…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we identified and incised the shallow MP layer and removed the tumour en bloc , including the MP. Biopsy forceps were used to extract the specimen [ 15 ]. When the tumour was too large to extract through the outer cylinder, we cut the surface of the tumour with a conventional loop‐type electrode ( n = 23).…”
Section: Methodsmentioning
confidence: 99%